USDA Nutrition Evidence Systematic Review’s collaborative approach for conducting systematic reviews: Promoting diversity of expertise while managing potential conflicts of interest - Obbagy, Julie; Raghavan, Ramkripa; Cole, Natasha Chong; English, Laural K.; Higgins, Molly; Spahn, Joanne M.; Bahnfleth, Charlotte L.; Callahan, Emily; Fultz, Amanda; Kim, Julia H.; Kingshipp, Brittany J.; Nevins, Julie E. H.; et al. (Frontiers in Nutrition, 2023)
U.S. Department of Agriculture’s (USDA) Nutrition Evidence Systematic Review (NESR) Branch develops food- and nutrition-related systematic reviews and other evidence synthesis products. NESR has established itself as a key resource for the Federal government when making evidence-informed decisions related to public health nutrition, such as the development of the Dietary Guidelines for Americans. NESR’s systematic review methodology is rigorous, protocol-driven, and highly collaborative. NESR’s systematic reviews examine the complex interplay between diet and health with input and support from various collaborators, including Federal stakeholders, expert groups, and public stakeholders. Implementing NESR’s rigorous methodology ensures that the appropriate steps are taken to minimize conflict of interest, producing systematic reviews that are high-quality, trustworthy, and useful to end users who make decisions based on their findings. This article describes how NESR's systematic review process leverages a diversity of expertise and experience, while managing potential biases and conflicts of interest. It describes the groups who collaborate to conduct NESR systematic reviews, their expertise, and why their involvement is critical for ensuring the rigor and utility of NESR’s work.